An integrated homogeneous SPARCL™ immunoassay for rapid biomarker detection on a chip. Issue 19 (26th April 2019) - Sandetskaya, Natalia; Isserstedt-John, Nicole; Kölsch, Andreas; Schattschneider, Sebastian; Kuhlmeier, Dirk
Abstract : A very simple and rapid homogeneous SPARCL™ immunoassay with on-chip preserved dry reagents enables sensitive quantitative detection of biomarkers. Abstract : We developed an integrated version of the homogeneous SPARCL™ (Spatial Proximity Analyte Reagent Capture Luminescence) immunoassay for rapid measurement of biomarkers on a chip. Our development is based on a simple microfluidic design with on-chip preserved dry reagents. The assay requires no washing steps and can be performed in a "mix-and-read" format. A syringe pump and a luminometer supported the detection. Only one manual pipetting step is necessary to load the sample onto the chip, and the entire incubation and measurement can be accomplished in approximately 35 min. We have demonstrated the application of the SPARCL™ on a chip to the quantitative detection of the tissue inhibitor of metalloproteinases 1 (TIMP-1) in spiked mock samples and a limited number of gingival crevicular fluid specimens. The integrated SPARCL™ assay could detect as little as 49.3 pg ml −1 (1.76 pM) TIMP1. To our knowledge, this is the first demonstration of the fully integrated homogeneous SPARCL™ immunoassay in a lab-on-a-chip. Further, we discuss the optimization of the chip and the assay in order to improve its analytical performance.